Analysis and mitigation of defective circular structures in HPCVD-grown MgB2 thin films. Issue 1 (February 2020) - Li, Y L; Kong, X D; Han, L
Abstract: In MgB2 films synthesized via hybrid physical-chemical vapor deposition, circular structures containing Mg microparticles were detected, with diameters ranging from 17 to 25 μm. The thinning of MgB2 film was observed inside these circular structures, which formation was found to be induced by rapid heating process and intense evaporation of Mg slugs. Tiny Mg droplets sputtering onto the substrates during rapid heating process influence the growth of MgB2 film and tend to form circular structures around Mg particles, which problem can be mitigated by slowing down the heating process. As a result, MgB2 films with smooth surfaces were obtained, which is instrumental in the fabrication of MgB2 film electronic devices.